Active ray-curable composition, active ray-curable ink composition and method for producing them

JP2025011680APending Publication Date: 2025-01-24NISSHIN CHEM IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023113926
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-24

AI Technical Summary

Benefits of technology

【0013】 本発明の活性光線硬化型組成物及び活性光線硬化型インキ組成物は、有機溶剤を含まず、柔軟性及び透明性に優れ、更に耐アルコール性·耐薬品性に優れる。従って、塗布や印刷の際に溶剤を熱乾燥させる工程が不要であり、環境に対する懸念も少ない。本発明の活性光線硬化型組成物は、優れた柔軟性及び透明性に優れた塗膜を提供するためプラスチック、紙、ガラス、木工及び無機材料等の塗料、コーティング剤、包装材料用、表示材料用、電子材料用あるいは光学材料用の硬化接着剤、スクリーン印刷、オフセット印刷、ロールコーター印刷、インクジェットインク、プライマーインク等の印刷インキ等の様々な用途に広く使用することが可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011680000001
    Figure 2025011680000001
  • Figure 2025011680000002
    Figure 2025011680000002
Patent Text Reader

Abstract

To provide an active ray-curable composition and an active ray-curable ink composition which contain no organic solvent, have excellent flexibility and transparency and also have excellent alcohol resistance and chemical resistance and a method for producing them.SOLUTION: There is provided an active ray-curable composition which comprises (I) a vinyl chloride-based copolymer having a unit derived vinyl chloride and a unit derived from vinyl acetate and having a degree of polymerization of 150 to 800 and (II) a photocurable monomer and / an oligomer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an actinic radiation-curable composition containing a vinyl chloride-vinyl acetate copolymer, an actinic radiation-curable ink composition, and methods for producing the same. [Background technology]

[0002] Conventionally, actinic radiation-curable compositions that are cured by actinic radiation such as ultraviolet rays or electron beams have been put to practical use in various applications such as paints, coating agents, adhesives, printing inks, ink-receptive layers, printed circuit boards, and electrical insulation for plastics, paper, glass, woodworking, and inorganic materials, etc. In particular, actinic radiation-curable inks have attracted attention due to their quick drying properties and the ability to record on recording media with poor ink absorbency.

[0003] Such actinic radiation-curable compositions are required to have excellent flexibility and adhesion, and therefore, various methods have been proposed to date for improving the flexibility and adhesion of actinic radiation-curable compositions.

[0004] For example, JP 2010-006878 A (Patent Document 1) discloses an active energy ray-curable ink composition in which an active energy ray-curable ink is mixed with a varnish in which a thermoplastic resin having a glass transition temperature of 50 to 250° C. is dissolved in a solvent.

[0005] However, since this active energy ray-curable ink composition contains a solvent, a step of thermally drying the solvent is essential, and furthermore, the solvent may remain in the ink after printing, which may have an adverse effect on the environment.

[0006] On the other hand, as an example of an actinic radiation-curable ink that does not contain a solvent, JP 2009-197156 A (Patent Document 2) discloses a cationic polymerization type inkjet ink that contains 0.3% by mass or more and 5.0% by mass or less of a vinyl chloride-vinyl acetate copolymer having a number average molecular weight of 14,000 or more and 25,000 or less.

[0007] However, although the cationic polymerization type inkjet ink described in Patent Document 2 is said to have excellent adhesion, there is room for improvement. In addition, the ink in Patent Document 2 has poor flexibility and is not suitable for applications requiring greater flexibility.

[0008] In addition, it is also important that actinic radiation curable compositions used for various applications have little deterioration over time and excellent thermal stability. JP2018-135483A (Patent Document 3) discloses an actinic radiation curable composition having excellent flexibility, adhesion, and thermal stability. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2010-006878 A [Patent Document 2] JP 2009-197156 A [Patent Document 3] JP 2018-135483 A Summary of the Invention [Problem to be solved by the invention]

[0010] However, although the actinic radiation-curable composition described in Patent Document 3 has high flexibility and adhesion, the transparency of the coating film may be poor and the coating film resistance, such as alcohol resistance, may be poor, leaving room for improvement. The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an actinic radiation-curable composition which does not contain an organic solvent, has excellent flexibility and transparency, and further has excellent alcohol resistance and chemical resistance, an actinic radiation-curable ink composition, and methods for producing the same. [Means for solving the problem]

[0011] As a result of extensive investigations to achieve the above object, the inventors have found that by dissolving a vinyl chloride-vinyl acetate copolymer in a photocurable monomer and / or oligomer, an actinic radiation-curable composition having excellent flexibility and transparency as well as excellent resistance to alcohol and chemicals can be obtained, and have thus completed the present invention.

[0012] That is, the present invention provides the following actinic radiation-curable composition and actinic radiation-curable ink composition. [1] An actinic radiation-curable composition comprising: (I) a vinyl chloride-based copolymer having a vinyl chloride-derived unit and a vinyl acetate-derived unit and having a degree of polymerization of 150 to 800; and (II) a photocurable monomer and / or oligomer. [2] The actinic radiation-curable composition according to the above [1], wherein the (II) photocurable monomer and / or oligomer is one or more monomers selected from the group consisting of monofunctional acrylates, difunctional acrylates, polyfunctional acrylates, monofunctional methacrylates, difunctional methacrylates, polyfunctional methacrylates, and urethane acrylates, and / or oligomers of such monomers. [3] The actinic radiation-curable composition according to the above [1] or [2], wherein the content of the vinyl chloride copolymer (I) is 1 to 30 mass% based on the total amount of the vinyl chloride copolymer (I) and the photocurable monomer and / or oligomer (II). [4] The actinic radiation-curable composition according to any one of the above [1] to [3], wherein the vinyl chloride copolymer contains (a) 75 to 95 mass% of vinyl chloride-derived units and (b) 1 to 25 mass% of vinyl acetate-derived units based on the total mass of the vinyl chloride copolymer. [5] The actinic radiation-curable composition according to any one of the above [1] to [4], which does not contain an organic solvent. [6] The actinic radiation-curable composition according to any one of the above [1] to [5], wherein the vinyl chloride copolymer (I) has a glass transition temperature of 60 to 80°C. [7] An actinic radiation-curable ink composition comprising the actinic radiation-curable composition according to any one of the above [1] to [6] and a pigment. [8] A coating film obtained by curing the actinic radiation-curable composition according to any one of the above [1] to [6]. [9] A coating film obtained by curing the actinic radiation-curable ink composition described in [7] above. Effect of the Invention

[0013] The actinic radiation curable composition and actinic radiation curable ink composition of the present invention do not contain organic solvents, have excellent flexibility and transparency, and further have excellent alcohol resistance and chemical resistance. Therefore, a process of thermally drying the solvent during application or printing is not required, and there are few environmental concerns. The actinic radiation curable composition of the present invention provides a coating film with excellent flexibility and transparency, and can be widely used in various applications such as paints for plastics, paper, glass, woodworking, and inorganic materials, coating agents, curable adhesives for packaging materials, display materials, electronic materials, and optical materials, screen printing, offset printing, roll coater printing, inkjet inks, primer inks, and other printing inks. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The actinic radiation-curable composition of the present invention is an actinic radiation-curable composition containing (I) a vinyl chloride-vinyl acetate copolymer having a degree of polymerization of 150 to 800, and (II) a photocurable monomer and / or oligomer.

[0015] (I) The vinyl chloride-vinyl acetate copolymer is a copolymer having a vinyl chloride-derived unit and a vinyl acetate-derived unit and having a degree of polymerization of 150 to 800, preferably 200 to 780. The degree of polymerization is an average degree of polymerization value calculated from the results of measuring the time required for a sample dissolved in nitrobenzene to fall at 30.0°C using an Ubbelohde viscometer.

[0016] (I) The glass transition temperature of the vinyl chloride-vinyl acetate copolymer is preferably 60 to 80°C. About 20 mg of the powdered vinyl chloride-vinyl acetate copolymer was measured using a Shimadzu DSC (differential scanning calorimeter) at a heating rate of 5 K / min. Looking at the second heating curve, a baseline shift was observed, and this is the value of the inflection point.

[0017] The constituent units of the vinyl chloride-vinyl acetate copolymer preferably contain (a) 75 to 95 mass % of units derived from vinyl chloride and (b) 1 to 25 mass % of units derived from vinyl acetate. More preferably, it is a copolymer containing the following components (a) to (d): (a) 75 to 95 mass% of vinyl chloride-derived units, (b) 1 to 25 mass% of vinyl acetate-derived units, (c) 0 to 20% by mass of vinyl alcohol-derived units, and (d) 0 to 20% by mass of vinyl-derived units other than the above components (a), (b) and (c)

[0018] Here, each of the vinyl-derived units, i.e., (a) vinyl chloride-derived units, (b) vinyl acetate-derived units, (c) vinyl alcohol-derived units, and (d) vinyl-derived units other than the above components (a), (b), and (c), is a unit constituting the vinyl chloride copolymer (I), and is composed of (a') vinyl chloride monomer, (b') vinyl acetate monomer, and (d') a vinyl monomer other than the above components (a), (b), and (c), respectively, and the (c) vinyl alcohol unit is a unit obtained by a saponification reaction of the (b) vinyl acetate-derived unit.

[0019] The (a) vinyl chloride-derived units impart toughness and high surface hardness to the coating film of the actinic radiation curable composition. The proportion of the (a) vinyl chloride-derived units in the (I) vinyl chloride-based copolymer is preferably 75 to 95 mass% and more preferably 77 to 94 mass% based on the total mass of the copolymer. If the proportion of the (a) vinyl chloride-derived units is less than the above lower limit, the glass transition point of the (I) vinyl chloride-based copolymer is low, making it difficult to maintain the particle shape. If the proportion of the (a) vinyl chloride-derived units exceeds the above upper limit, the solubility of the (I) vinyl chloride-based copolymer in the (II) photocurable monomer and / or oligomer decreases, and the transparency of the actinic radiation curable composition decreases.

[0020] The proportion of the vinyl acetate-derived units (b) in the vinyl chloride copolymer (I) is preferably 1 to 25 mass % based on the total mass of the copolymer, more preferably 1 to 23 mass %. If the proportion of the vinyl fatty acid-derived units (b) is less than the above lower limit, the solubility of the vinyl chloride copolymer (I) in the photocurable monomer and / or oligomer (II) decreases, and the transparency of the actinic radiation-curable composition also decreases. If the proportion of the vinyl acetate-derived units (b) exceeds the above upper limit, the glass transition point of the vinyl chloride copolymer (I) decreases, making it difficult to maintain the particle shape.

[0021] The copolymer of the present invention may contain (c) vinyl alcohol-derived units. The vinyl alcohol-derived units are units obtained by saponification reaction of (b) vinyl acetate-derived units as described above. The proportion of (c) vinyl alcohol-derived units in the vinyl chloride copolymer is preferably 0 to 20% by mass based on the total mass of the copolymer. When contained, the lower limit is preferably 1% by mass or more. The upper limit is preferably 15% by mass or less, more preferably 14% by mass or less.

[0022] The vinyl chloride copolymer (I) may contain, as component (d), vinyl-derived units other than the above components (a), (b) and (c), as necessary. Examples of the vinyl-derived units other than the (a), (b) and (c) components in the (d) component include units derived from methyl glycidyl methacrylate, methyl glycidyl acrylate, allyl glycidyl ether, allylphenol glycidyl ether, glycidyl methacrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polyethylene glycol polypropylene glycol mono(meth)acrylate, glycerol mono(meth)acrylate, glycerol monoallyl ether, hydroxyethyl vinyl ether, ethylene glycol monoallyl ether, hydroxybutyl vinyl ether, (meth)allyl alcohol, N-methylol (meth)acrylamide, epoxy group-containing vinyl, styrene, α-methylstyrene, acrylonitrile, alkyl (meth)acrylates such as methyl (meth)acrylate and ethyl (meth)acrylate, acrylic acid, methacrylic acid, maleic anhydride, crotonic acid, itaconic acid, vinylidene chloride, etc. Two or more of these units may be included.

[0023] In addition, the vinyl-derived units other than the components (a), (b) and (c) as the component (d) are preferably contained in the vinyl chloride copolymer (I) at a ratio of 0 to 20% by mass, as long as the effect of the present invention is not impaired. The amount of other vinyl-derived units is preferably 0 to 15% by mass. In particular, when epoxy-group-containing vinyl-derived units such as methyl glycidyl methacrylate, methyl glycidyl acrylate, allyl glycidyl ether, allylphenol glycidyl ether and glycidyl methacrylate are contained, the amount is preferably less than 2.5% by mass and is preferably 1% by mass or less.

[0024] The desired vinyl chloride-vinyl acetate copolymer (I) may be manufactured or a commercially available product may be used. Commercially available products include the Solvine series manufactured by Nissin Chemical Industry Co., Ltd., the VINNOL series manufactured by Wacker, and the Kanevinyl series manufactured by Kaneka Corporation. It may also be manufactured by the method described below.

[0025] The method for producing the vinyl chloride copolymer (I) is not particularly limited. For example, at least (a') vinyl chloride monomer, (b') vinyl acetate monomer, and, if necessary, (d') vinyl monomer other than the above components (a') and (b') are copolymerized, and during the copolymerization reaction, the vinyl chloride monomer (a') is further added to produce the following components (a) to (d) as structural units relative to the mass of the vinyl chloride copolymer: (a) 75 to 95 mass% of vinyl chloride-derived units, (b) 1 to 25 mass% of vinyl acetate-derived units, (d) 0 to 15% by mass of vinyl-derived units other than the above components (a), (b) and (c) It is possible to obtain a vinyl chloride copolymer (I) containing the above compound.

[0026] In addition, in the case of producing a vinyl chloride-vinyl acetate copolymer containing vinyl alcohol units (c), At least (a') vinyl chloride monomer, (b') fatty acid vinyl monomer, and, if necessary, (d') vinyl monomer other than the above components (a') and (b') are copolymerized, and during the copolymerization reaction, (a') vinyl chloride monomer is further added, followed by a saponification reaction to produce the following components (a) to (d) as constituent units relative to the mass of the vinyl chloride copolymer: (a) 75 to 95 mass% of vinyl chloride-derived units, (b) 1 to 25 mass% of vinyl acetate-derived units, (c) 1 to 15 mass% of vinyl alcohol-derived units, and (d) 0 to 15% by mass of vinyl-derived units other than the above components (a), (b) and (c) It is possible to obtain a vinyl chloride copolymer (I) containing the above compound.

[0027] In addition, each monomer as a raw material may be charged at once before the start of the copolymerization reaction, but some monomers may be added during the copolymerization reaction. The vinyl chloride monomer (a') as a raw material is preferably added during the copolymerization reaction separately from the amount charged before the start of the copolymerization reaction, and the vinyl chloride monomer (a') is preferably added after the temperature is raised. It is preferable that 40 to 80 mass % of the vinyl chloride monomer (a') used as a raw material is added. In this way, a vinyl chloride copolymer (I) having excellent thermal stability and solubility in photocurable monomers and / or oligomers (II) can be obtained.

[0028] The copolymerization reaction is preferably carried out by suspension polymerization. In detail, after the inside of the polymerization vessel is replaced with nitrogen, a polymerization medium, a suspending agent, a polymerization initiator, (a') vinyl chloride monomer, (b') fatty acid vinyl monomer, and (d') vinyl monomer other than (a') and (b') as necessary are pressurized. Then, the temperature is raised to an appropriate polymerization temperature, and the copolymerization reaction is started under a nitrogen atmosphere. During this copolymerization reaction, each monomer serving as a raw material may be additionally added.

[0029] Examples of the suspending agent include polyvinyl alcohol, partially saponified polyvinyl acetate, cellulose derivatives such as methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, and hydroxyethyl cellulose, synthetic polymers such as polyvinylpyrrolidone, polyacrylamide, maleic acid-styrene copolymer, and maleic acid-methyl vinyl ether copolymer, natural polymers such as starch and gelatin, polyalkylene oxides such as polyethylene oxide and polypropylene oxide, and oxyethylene-oxypropylene block copolymers. These may be used in combination of two or more kinds.

[0030] The weight average molecular weight of the suspending agent is preferably 50,000 to 5,000,000. For example, polyalkylene oxides such as polyethylene oxide and polypropylene oxide can be suitably used as the suspending agent. The amount of the suspending agent used is preferably 0.05 to 0.3% by mass based on the total amount of the raw material monomers.

[0031] Examples of the polymerization initiator include organic peroxides such as benzoyl peroxide, lauroyl peroxide, 3,3,5-trimethylhexanol peroxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, diethoxyethyl peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, butyl peroxyneodecanate, and di-3,5,5-trimethylhexanol peroxide, and azo compounds such as azobisisobutyronitrile and 2,2-azobis(2,4-dimethyl)valeronitrile. Two or more of these may be used in combination. The amount of the polymerization initiator used is preferably 0.1 to 0.3% by mass based on the total amount of the raw material monomers.

[0032] Ion-exchanged water can be used as the polymerization medium. Alternatively, a polymerization medium containing water-soluble alcohol such as methanol or isopropyl alcohol at a ratio of 50% by mass or less may be used. The amount of the polymerization medium used is preferably 50 to 200% by mass based on the total amount of the raw material monomers.

[0033] A chain transfer agent may be used in the copolymerization reaction during the production of the vinyl chloride copolymer (I). As the chain transfer agent, a dihydrooxaphosphaphenanthrene phosphorus compound having a cyclic organic phosphorus compound is preferred. The amount of the chain transfer agent used is preferably 0.3 to 0.6 mass% based on the total amount of the raw material monomers, and more preferably 0.4 to 0.5 mass%. If the amount of the chain transfer agent used is less than 0.3 mass%, the viscosity of the actinic radiation curable composition tends to increase, which may make handling difficult and reduce workability. If the amount of the chain transfer agent used exceeds 0.6 mass%, the physical strength and durability of the coating film of the actinic radiation curable composition may decrease.

[0034] (I) In the copolymerization reaction for producing the vinyl chloride copolymer, the suspending agent, polymerization initiator, chain transfer agent, etc. may be charged all at once before the start of the copolymerization reaction, or may be added during the copolymerization reaction. The polymerization temperature is preferably 50 to 80°C, more preferably 55 to 75°C.

[0035] The vinyl chloride copolymer (I) obtained by the above copolymerization reaction is preferably separated from the polymerization medium, dried, and powdered. The average particle size of this vinyl chloride copolymer powder is preferably 50 to 500 μm. The average particle size is a value measured using a laser diffraction / scattering type particle size distribution measuring device, for example, LA-950V2 (manufactured by HORIBA).

[0036] The average degree of polymerization of the vinyl chloride copolymer (I) is preferably 150 to 800, and more preferably 200 to 780. This average degree of polymerization is a value calculated from the results of measuring the time required for a sample dissolved in nitrobenzene to fall at 30.0°C using an Ubbelohde viscometer.

[0037] (I) The number average molecular weight of the vinyl chloride copolymer is preferably at least 20,000, and more preferably at least 25,000. The number average molecular weight is a value measured using a molecular weight distribution analyzer, for example, "GPC-900" manufactured by JASCO Corporation.

[0038] The actinic radiation-curable composition of the present invention contains (I) a vinyl chloride copolymer and (II) a photocurable monomer and / or oligomer.

[0039] The photocurable monomer and / or oligomer, which is the component (II), is a monomer and / or oligomer that can be polymerized and cured by light having a specific wavelength. As the component (II), those that can be polymerized and cured by ultraviolet light are particularly preferred.

[0040] The (II) photocurable monomer and / or oligomer may be radically polymerizable, cationic polymerizable, or anionic polymerizable, but is preferably radically polymerizable. The (II) photocurable monomer and / or oligomer is preferably one or more monomers selected from the group consisting of monofunctional acrylates, bifunctional acrylates, polyfunctional acrylates, monofunctional methacrylates, bifunctional methacrylates, polyfunctional methacrylates, and urethane acrylates.For example, 2-phenoxyethyl acrylate, 2-hydroxy-3-acryloyloxypropyl methacrylate, polyethylene glycol diacrylate, propoxylated ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, tricyclodecane dimethanol diacrylate, 1,10-decanediol diacrylate, 1,6-hexanediol diacrylate (HDDA), 1,9-nonanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate (TPGDA), polytetramethylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, ethoxylated bisphenol A dimethacrylate, tricyclodecane dimethacrylate, Examples of the monomer include methanol dimethacrylate, 1,10-decanediol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, neopentyl glycol dimethacrylate, ethoxylated polypropylene glycol dimethacrylate, glycerin dimethacrylate, polypropylene glycol dimethacrylate, ethoxylated isocyanuric acid triacrylate, ε-caprolactone modified tris-(2-acryloxyethyl)isocyanurate, pentaerythritol triacrylate, trimethylolpropane triacrylate (TMPTA), ditrimethylolpropane tetraacrylate, ethoxylated pentaerythritol tetraacrylate, pentaerythritol tetraacrylate, dipentaerythritol polyacrylate, dipentaerythritol hexaacrylate, and trimethylolpropane trimethacrylate. In addition, the monomer may be an oligomer. In this case, the oligomer generally has a degree of polymerization of 10 to 100.

[0041] The actinic radiation curable composition of the present invention preferably contains a photopolymerization initiator together with (II) photocurable monomer and / or oligomer. The photopolymerization initiator generates active species by irradiation with light of a characteristic wavelength, and a suitable one can be selected from photoradical polymerization initiators, photocationic polymerization initiators, and photoanionic polymerization initiators depending on the type of (II) photocurable monomer and / or oligomer. In particular, it is preferable to use a photoradical polymerization initiator that generates radicals by ultraviolet light. Examples of such photopolymerization initiators include alkylphenone-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, intramolecular hydrogen abstraction-type photopolymerization initiators, and oxime ester-based photopolymerization initiators. Among them, alkylphenone-based photopolymerization initiators are preferred, and in particular, 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-methyl-1-(4-morpholinophenyl)-2-propan-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, etc. More preferably, α-hydroxyalkylphenone-based photopolymerization initiators such as 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one are preferred. Commercially available initiators include IRUGACURE184, 1173, 2959, and 127 manufactured by BASF.

[0042] The photopolymerization initiator is preferably contained in an amount of 1 part by mass or more, more preferably 1 to 10 parts by mass, based on 100 parts by mass of the total amount of (I) the vinyl chloride copolymer and (II) the photocurable monomer and / or oligomer. If the content is less than 1 part by mass, the actinic radiation curable composition may not be cured.

[0043] The actinic radiation curable composition of the present invention can be obtained by dispersing or dissolving (I) vinyl chloride copolymer in (II) photocurable monomer and / or oligomer. (I) vinyl chloride copolymer is preferably contained in an amount of 1 to 30 mass%, more preferably 20 to 30 mass%, based on the total amount of (I) vinyl chloride copolymer and (II) photocurable monomer and / or oligomer. If the content of (I) vinyl chloride copolymer is less than 1 mass%, the desired effects in flexibility, adhesion, thermal stability, etc. may not be sufficiently obtained. If the content exceeds 30 mass%, (I) vinyl chloride copolymer may not dissolve or the viscosity may become too high.

[0044] The temperature at which (I) the vinyl chloride copolymer is dispersed and dissolved in (II) the photocurable monomer and / or oligomer is preferably 30 to 80°C.

[0045] An actinic radiation curable ink composition can be obtained by dispersing and incorporating a pigment in the actinic radiation curable composition of the present invention. The pigments used are, in terms of color index, Pigment White 4, Pigment White 6, Pigment White 21, Pigment Black 7 (carbon black), Pigment Blue 15, 15:1, 15:3, 15:4, 15:6, 60, Pigment Green 7 (chlorinated phthalocyanine green), 36 (brominated phthalocyanine green), Pigment Red 9, 48, 49, 52, 53, 57, 57:1, 97, 122, 149, 168, 177, 178, 179, 206, 207, 209, 242, 254, 255, Pigment Violet 19, 23, 29, 30, 37, 40, 50, Pigment Yellow 12, 13, 14, 17, 20, 24, 74, 83, 86, 93, 94, 95, 109, 110, 117, 120, 125, 128, 137, 138, 139, 147, 148, 150, 151, 154, 155, 166, 168, 180, 185, 213, Pigment Orange 36, 43, 51, 55, 59, 61, 71, 74, and the like.

[0046] The blending amount of the pigment is appropriately selected depending on the type of pigment, but is usually in the range of 10 to 20 parts by mass per 100 parts by mass of the actinic radiation-curable composition.

[0047] For dispersing the pigment, for example, a ball mill, a sand mill, an attritor, a roll mill, an agitator, a Henschel mixer, a colloid mill, an ultrasonic homogenizer, a pearl mill, a wet jet mill, a paint shaker, or the like can be used.

[0048] The actinic radiation curable composition and actinic radiation curable ink composition of the present invention can be applied onto a substrate by a known method such as spin coating, (doctor) knife coating, microgravure coating, direct gravure coating, offset gravure, reverse gravure, reverse roll coating, (Mayer) bar coating, die coating, spray coating, or dip coating.

[0049] Furthermore, the actinic radiation curable composition and actinic radiation curable ink composition of the present invention can be irradiated with light of a specific wavelength to cure the coating. In this case, the light is preferably ultraviolet light, and the irradiation conditions are an irradiation intensity of 150 to 1,000 mJ / cm. 2 The irradiation time is preferably 1 to 1000 seconds.

[0050] The thickness of the coating film may be appropriately set depending on the purpose, but from the viewpoints of cost and performance, it is preferably 0.5 to 200 μm, and more preferably 1.5 to 100 μm.

[0051] The actinic radiation curable composition and actinic radiation curable ink composition of the present invention can be applied to substrates such as plastics such as polyethylene terephthalate (PET), oriented polystyrene (OPS), oriented polypropylene (OPP), oriented nylon (ONy), polyvinyl chloride (PVC), polyethylene (PE), triacetyl cellulose (TAC), polycarbonate, acrylic resin, ABS, polyacetal, polyvinyl alcohol (PVA), and rubbers, as well as metals, paper, wood, glass, and the like.

[0052] Members having a coating film of the actinic radiation-curable composition or the actinic radiation-curable ink composition formed on such a substrate are useful, for example, as flooring materials, floor tiles, various plastic products, beverage cans, metal plates, printed paper, paper containers, record jackets, magazines, aluminum-deposited paper, furniture, wall materials, building materials, optical applications, and the like. EXAMPLES

[0053] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, "parts" refers to "parts by mass".

[0054] [Example 1] 20 parts of (II) vinyl chloride-vinyl acetate copolymer (Solvine C5R, manufactured by Nissin Chemical Industry Co., Ltd.) was mixed with 80 parts of (II-I) Miramer M140 (2-phenoxyethyl acrylate, manufactured by MIWON Co., Ltd.) at 60°C for 3 hours to obtain a solution. Furthermore, 5 parts of 1-hydroxycyclohexyl phenyl ketone (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) was mixed as a photopolymerization initiator at 60°C for 1 hour to obtain an actinic radiation curable composition.

[0055] [Examples 2 to 11] The method described in Example 1 was repeated except that the raw materials shown in Table 1 were used, to obtain actinic radiation-curable compositions.

[0056] [Comparative Example 1] (II-III) 100 parts of Miramer M200 (1,6-hexanediol diacrylate, manufactured by MIWON Co., Ltd.) was mixed with 5 parts of 1-hydroxycyclohexyl phenyl ketone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a photopolymerization initiator at 60°C for 1 hour to obtain an actinic radiation curable composition.

[0057] [Comparative Example 2] 20 parts of (I-VII) acrylic resin (Dianal BR-117, manufactured by Mitsubishi Chemical Corporation) was dissolved in 80 parts of (II-II) Miramer M1182 (benzyl acrylate, manufactured by MIWON Corporation) by stirring at 60° C. for 3 hours. Furthermore, 5 parts of 1-hydroxycyclohexyl phenyl ketone (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a photopolymerization initiator was mixed at 60° C. for 1 hour to obtain an actinic radiation curable composition.

[0058] [Comparative Example 3] 20 parts of (I-VII) acrylic resin (Dianal BR-117, manufactured by Mitsubishi Chemical Corporation) was dissolved in 80 parts of (II-III) Miramer M200 (1,6-hexanediol diacrylate, manufactured by MIWON Corporation) by stirring at 60° C. for 3 hours. Furthermore, 5 parts of 1-hydroxycyclohexyl phenyl ketone (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) as a photopolymerization initiator was mixed at 60° C. for 1 hour to obtain an actinic radiation curable composition.

[0059] The obtained actinic radiation curable composition was measured for solubility, coating film transparency, coating film elongation and coating film resistance by the following methods. The results are shown in Table 1.

[0060] ·Solubility In order to confirm the solubility of solutions prepared by dissolving various vinyl chloride-vinyl acetate copolymers and acrylic resins in various acrylic monomers to a solid content of 20 mass %, a piece of paper with writing on it was placed against the background and visually confirmed through the solution whether the writing was visible. (Evaluation Criteria) ○ When the solvent is applied, the text on the back is clearly visible. △ When the solvent is applied, the text behind the image becomes blurred. ×: When the solvent is passed through the label, the text on the back is barely visible.

[0061] ·Coating film transparency The actinic radiation curable composition obtained above was applied onto a PET film (manufactured by Toray Industries, Inc.) using a bar coater #10, and irradiated with ultraviolet light at a wavelength of 385 nm. The irradiation time was 5 minutes for the monofunctional acrylic monomer solutions (II-I) and (II-II), and 10 minutes for the bifunctional acrylic monomer solutions (II-III) and (II-VI). The haze value of the film on which the coating was formed was measured using a color difference / turbidity meter COH-400 (manufactured by Nippon Denshoku Industries Co., Ltd.). The smaller the haze value, the higher the transparency of the film. The haze value when a coating (film thickness after curing: 12 to 20 μm) is formed using a bar coater #10 is preferably 3.0% or less, more preferably 1.0% or less.

[0062] ·Paint film elongation rate The actinic radiation curable composition obtained above was applied onto a glass plate using a 4 mil doctor knife and irradiated with ultraviolet light of 385 nm wavelength. The irradiation time was 5 minutes for the monofunctional acrylic monomer solution (II-I) and (II-II), and 10 minutes for the bifunctional acrylic monomer solution (II-III) and (II-VI). The coating film peeled off from the glass plate was cut into a width of 20 mm to prepare a sample. A tensile test was performed on the prepared sample at 10 mm / min using a tensile tester (manufactured by NMB). The elongation and tensile strength of the coating film were calculated from the following formula. The elongation is required to be 1% or more. Elongation rate = 100 × ΔL / L [%] Tensile strength=F / S [kgf / mm 2 ] L: length of sample S: cross-sectional area of ​​the sample ΔL: Length of elongation until the sample breaks F: The tensile force when the sample is elongated by ΔL and breaks

[0063] [Paint film resistance test] Alcohol resistance test The actinic radiation curable composition was applied onto a PET film (manufactured by Toray Industries, Inc.) using a bar coater #32, and irradiated with ultraviolet light having a wavelength of 385 nm for 10 minutes. At this time, the film thickness after curing was 75 μm. The film on which the coating film was formed was immersed in a 65% ethanol solution for one week, and the whitening of the coating film before and after immersion and the presence or absence of adhesion due to immersion were confirmed. (Evaluation Criteria) ○ No change in coating condition after immersion for one week △: After one week of immersion, the coating is uneven and liquid has penetrated into the substrate. ×...Paint film peels off and whitens after immersion for one week.

[0064] Acid resistance test The film on which the coating was formed in the same manner as above was immersed in a 10% HNO3 solution for one week, and the whitening of the coating film before and after immersion and the presence or absence of adhesion due to immersion were confirmed. (Evaluation Criteria) ○ No change in coating condition after immersion for one week △: After one week of immersion, the coating is uneven and liquid has penetrated into the substrate. ×...Paint film peels off and whitens after immersion for one week.

[0065] Alkaline resistance test The film on which the coating film was formed in the same manner as above was immersed in a 10% NaOH solution for one week, and the whitening of the coating film before and after immersion and the presence or absence of adhesion due to immersion were confirmed. (Evaluation Criteria) ○ No change in coating condition after immersion for one week △: After one week of immersion, the coating is uneven and liquid has penetrated into the substrate. ×...Paint film peels off and whitens after immersion for one week.

[0066] The vinyl chloride-vinyl acetate copolymer, acrylic resin and acrylic monomer used in the examples and comparative examples are as follows. (II) Solvine (registered trademark) C5R (manufactured by Nissin Chemical Industry Co., Ltd., vinyl chloride-vinyl acetate copolymer, average degree of polymerization 350, Tg 64°C) Vinyl chloride derived units: 79% by mass, vinyl acetate derived units: 21% by mass (I-II) Solvine (registered trademark) CL (manufactured by Nissin Chemical Industry Co., Ltd., vinyl chloride-vinyl acetate copolymer, average degree of polymerization 300, Tg 68°C) Vinyl chloride derived units: 86% by mass, vinyl acetate derived units: 14% by mass (I-III) Solvine (registered trademark) M5R (manufactured by Nissin Chemical Industry Co., Ltd., vinyl chloride-vinyl acetate copolymer, average degree of polymerization 390, Tg 64°C) Vinyl chloride derived units: 77% by mass, vinyl acetate derived units: 22% by mass, other units (dicarboxylic acid derived units): 1% by mass (I-IV) Solvine (registered trademark) TA3 (manufactured by Nissin Chemical Industry Co., Ltd., vinyl chloride-vinyl acetate copolymer, average degree of polymerization 350, Tg 64°C) Vinyl chloride derived units: 83% by mass, vinyl acetate derived units: 4% by mass, hydroxypropyl acrylate: 13% by mass (IV) Solvine (registered trademark) AL (manufactured by Nissin Chemical Industry Co., Ltd., vinyl chloride-vinyl acetate copolymer, average degree of polymerization 300, Tg 74°C) Vinyl chloride derived units: 92.5% by mass, vinyl acetate derived units: 2.5% by mass, vinyl alcohol derived units: 5% by mass (I-VI) Solvine (registered trademark) ALLP (manufactured by Nissin Chemical Industry Co., Ltd., vinyl chloride-vinyl acetate copolymer, average degree of polymerization 260, Tg 75°C) Vinyl chloride derived units: 92% by mass, vinyl acetate derived units: 1% by mass, vinyl alcohol derived units: 7% by mass (I-VII) DIANAL (registered trademark) BR-117 (manufactured by Mitsubishi Chemical Corporation, acrylic resin, Tg 34°C, Mw: 140,000) (II-I) Miramer M140 (2-phenoxyethyl acrylate, manufactured by MIWON) (II-II) Miramer M1182 (benzyl acrylate, manufactured by MIWON) (II-III) Miramer M200 (1,6-hexanediol diacrylate, manufactured by MIWON) (II-IV) Miramer M220 (tripropylene glycol diacrylate, manufactured by MIWON)

[0067] [Table 1]

[0068] [Table 2]

Claims

1. An actinic radiation-curable composition comprising: (I) a vinyl chloride-based copolymer having a vinyl chloride-derived unit and a vinyl acetate-derived unit and having a degree of polymerization of 150 to 800; and (II) a photocurable monomer and / or oligomer.

2. 2. The actinic radiation-curable composition according to claim 1, wherein the (II) photocurable monomer and / or oligomer is one or more monomers selected from the group consisting of monofunctional acrylates, difunctional acrylates, polyfunctional acrylates, monofunctional methacrylates, difunctional methacrylates, polyfunctional methacrylates, and urethane acrylates, and / or oligomers of such monomers.

3. 2. The actinic radiation curable composition according to claim 1, wherein the content of the vinyl chloride copolymer (I) is 1 to 30 mass% based on the total amount of the vinyl chloride copolymer (I) and the photocurable monomer and / or oligomer (II).

4. 2. The actinic radiation-curable composition according to claim 1, wherein the vinyl chloride copolymer contains (a) 75 to 95 mass% of vinyl chloride-derived units and (b) 1 to 25 mass% of vinyl acetate-derived units based on the total mass of the vinyl chloride copolymer.

5. 2. The actinic radiation curable composition according to claim 1, which does not contain an organic solvent.

6. 2. The actinic radiation curable composition according to claim 1, wherein the vinyl chloride copolymer (I) has a glass transition temperature of 60 to 80°C.

7. 7. An actinic radiation-curable ink composition comprising the actinic radiation-curable composition according to any one of claims 1 to 6 and a pigment.

8. A coating film obtained by curing the actinic radiation-curable composition according to any one of claims 1 to 6.

9. A coating film obtained by curing the actinic radiation-curable ink composition according to claim 7.

Citation Information

Patent Citations

  • Cationic polymerization inkjet ink and inkjet recording method

    JP2009197156A

  • Active energy ray curable ink composition, print sheet and print sheet molded product

    JP2010006878A

  • Active ray curable composition, active ray-curable ink composition and method for producing them

    JP2018135483A